Corporate social responsibility and firm performance from developing markets: The role of audit committee expertise - Hariem Abdullah (Sustainable Futures)
This study investigates the complex relationship between CSR practices, firm financial performance, and the moderating role of audit committee expertise in the UAE, a high-speed developing market. Using a quantitative research design, we examine data from non-financial firms listed on the ADX over the period 2008–2022. We evaluate the effect of CSR on financial performance using a range of regression methods, and we look at the ways in which the experience of audit committee members strengthens or weakens this link. Our findings are consistent with the theory that CSR initiatives have a detrimental impact on UAE firms' financial performance. Moreover, empirical data points to the strengthening of the correlation between financial performance and CSR by audit committee expertise. When it comes to coordinating CSR activities with long-term sustainability objectives, the audit committee is essential. This study employs secondary data and focuses exclusively on the United Arab Emirates, even though it advances knowledge about corporate social responsibility (CSR) and firm performance in developing markets. Future research should consider broader geographical contexts and longer periods to enhance the generalizability of findings. Our findings offer practical insights for firms operating in developing markets, highlighting the impact of CSR on performance and the importance of audit committee expertise in maximising its impact. We encourage companies to improve their level of measurement and reporting, with the goal of effectively communicating and realising the potential benefits of CSR. This research extends the literature on CSR and firm performance by examining a high-speed developing market and providing guidance to firms operating in similar contexts. It emphasises the crucial role of audit committee expertise in realising the financial benefits of CSR practices.